Personal protective equipment (PPE) usage in construction projects: A scientometric approach. (March 2021) - Ammad, Syed; Alaloul, Wesam Salah; Saad, Syed; Qureshi, Abdul Hannan
Abstract: Health and safety are essential for construction project success where the negligence leads towards project failure. This study probes into Personal Protective Equipment (PPE) safety ventures associated with the construction projects. Initially, the literature was acquisition via three databases: Web of Science, Scopus and Science Direct, in addition to Google Scholar as a search engine. Keyword co-occurrence was performed on the selected articles returning 13 clusters, which were analysed via a manual method of articles selection. JIGSAW software was also implemented for a deeper conceptual understanding of articles corresponding literature. The extracted articles were then classified into four categories: Safety Education, Safety Management, Accident Prevention, and PPE Quality. Based on these classifications, the study provides a conceptual framework incorporating the critical success factors for PPE's usage and its implementation within the construction projects. PPE misuse is often neglected because the current assessment is mainly focused on visible outcomes such as critical injuries and accidents, and it is hard to identify hazardous behaviours in time. A future-directed framework for PPE, CARWIQS, was also created to mitigate the possible threats through its application in construction projects. Highlights: Health and safety are essential for construction project success. This study probes into PPE safety ventures associated with the construction projects. PPE misuse is often neglected on construction sites. A framework for PPE and CARWIQS was created to mitigate the possible threats.